Effect of Health Qigong-Baduanjin on the Balance Function of College Students - Moyi LI; Xiulu LAN; Xinghui YAN; Qiu LIN; Guohua ZHENG (康复学报)
Objective:To evaluate the effect of Health Qigong-Baduanjin on the balance function of college students.Methods:A total of 222 college students from Fujian University of Traditional Chinese Medicine were recruited and randomly allocated into Baduanjin or control group with a ratio of 1: 1. Participants in Baduanjin group were gathered to receive a 12-week Baduanjin training (1 hour per day and 5 days per week) during intervention period, while the control group received no special intervention. Follow-up period lasted 12 week after intervention period. Both groups received no intervention during follow-up period. The balance function was evaluated at baseline, at the end of 12-week intervention (at the 13th week of the study), and after the 12-week follow-up period (during the 25th week of the study).Results:The opened eyes and closed eyes indexes showed no differences between the two groups at baseline. At the end of the intervention period, the Opened Eyes Standard Deviation in Baduanjin group was significantly lower than control group (P<0.05). However, the differences in balance function indexes were not significant between the two groups after follow-up period.Conclusion:12-week Health Qigong-Baduanjin could have a positive effect for college students on balance function, but long term effect was not observed.